Unique North American isolates of severe metastatic hypervirulent Klebsiella pneumoniae strain infections with hepatic abscesses seen in young patients within Texas. - Junaid M Alam; Eric N Riha; Haris Ahmed; Hong M Thai; Kevin Garnepudi; Ramesh B Kesavan; Gnananandh Jayaraman; Anna Sangster; Dylan Curry; Heidi A Butz; Lori Smith; Maureen Vowles; et al. (PLoS ONE)
Rationale Hypervirulent Klebsiella pneumoniae (hvKp) infections have principally been identified in Asia. Within a two-month period, two patients between the ages of 30 to 50 years old presented to a tertiary referral hospital in Texas with septic shock, hepatic abscess, and septic thrombophlebitis. Blood cultures were positive for Klebsiella pneumoniae (isolates 2020CK-00441 and 2021CK-00720 respectively). The first patient survived after a prolonged hospital course while the second patient expired. Objectives Describe the clinical presentation of these two patients. Perform whole genome sequencing and bioinformatic analysis to evaluate potential outbreak of specific hvKp bacteria isolates. Methods Whole genome sequencing was performed using both paired-end Illumina MiSeq and nanopore sequencing to obtain a Completed genome for both isolates. Main results 2020CK-00441 belonged to ST23 type while 2021CK-00720 was a ST65 type isolate. Kleborate analyses predicted with high confidence both isolates were hvKp. Phylogenetic analyses showed the two strains are not closely related to each other nor to any known hvKp isolates reported. Both isolates had yersiniabactin, colibactin, aerobactin and salmochelin producing loci which likely confer these isolates hvKp phenotype. 2020CK-00441 and 2021CK-00720 had a unique pK2044 like plasmid. Conclusions HvKp strains capable of causing devastating metastatic septic infections have emerged in Texas. These isolates are unique compared to other hvKp strains globally. Country-wide surveillance and whole genome sequencing of these strains is essential to prevent a major public health emergency in the USA.